Identification of harmonics of RF field, which is used for production and heating of plasma in the torsatron "U-3M" - Berezhnyj, V.L.; Ocheretenko, V.L.; Pavlichenko, O.S.; Pinos, I.B.; Prokopenko, A.V.; Tsybenko, S.A.; Lozin, A.V. (Вопросы атомной науки и техники, 2006)
Experimental and numerical methods were used to identify the harmonics of the RF field used for plasma production and heating in the torsatron “U-3M”.